Investigating the association of microRNA polymorphisms and lifestyle factors with the susceptibility to common gastrointestinal cancers in an Indian population- A case control study - Charles Emmanuel Jebaraj Walter; Zioni Sangeetha Shankaran; Sai Sushmitha Kontham; Kotteeswaran Ramachandran; Nandini Prakash; Thanka Johnson; Sri Nisha JR (Heliyon)
The cancers of the gastrointestinal (GI) tract have become a common diagnosis worldwide contributing to a large number of mortalities. Though potentially curable they are mostly fatal due to late diagnosis and lack of accurate diagnostic markers. microRNA, micromanagers of gene expression have been associated to have distinct roles as oncogenes or tumour suppressors in several cancers including GI cancers. These miRNAs are known to harbour single nucleotide polymorphisms (SNPs) that lead to loss or gain of its functions and have been found to be associated with altering susceptibility of several cancers. The current study aimed to investigate the role of miRSNPs in common gastrointestinal cancers. A case control study was designed which included 210 GI cancer cases and 230 cancer free controls. The miRSNPs were successfully genotyped using MassARRAY technique. Association analysis revealed that miR-196a; rs11614913, pre-mir-423; rs6505162, pre-mir-605; rs2043556, pre-mir-149; rs2292832 and pri-mir-30c; rs928508 polymorphisms significantly altered the risk of common GI cancers. Multifactor dimensionality reduction analysis demonstrated that miRSNPs alter GI cancer risk by interacting with exposures like diabetes mellitus, alcohol consumption, diet and socioeconomic status in the study subjects. In conclusion it was found that presence of miRNA polymorphism and certain lifestyle factors alters susceptibility to GI cancers significantly.